Impact of star activity on exoplanet habitability - Valio, Adriana (Cadernos de Astronomia, 2022)
The Sun as well as the stars exhibit magnetic activity in the form of dark spots on their surface, in addition they also produce flares and mass ejections from their atmospheres. The signatures of dark spots on the surface of stars can be modeled so as to characterize their sizes and temperatures. Young and M dwarf stars produce energetic superflares, which can impact orbiting planets, especially those very close to their host star. The flux of ultraviolet radiation from these flares can be very harmful to potential organisms living on the surface of exoplanets orbiting in the habitable zone of active stars. However, an atmosphere with ozone could protect them, or perhaps an ocean. Winds also affect the planetary atmospheres and may be responsible for their erosion.